2013
DOI: 10.1155/2013/147097
|View full text |Cite
|
Sign up to set email alerts
|

Sparse Planar Array Synthesis Using Matrix Enhancement and Matrix Pencil

Abstract: The matrix enhancement and matrix pencil (MEMP) plays important roles in modern signal processing applications. In this paper, MEMP is applied to attack the problem of two-dimensional sparse array synthesis. Firstly, the desired array radiation pattern, as the original pattern for approximating, is sampled to form an enhanced matrix. After performing the singular value decomposition (SVD) and discarding the insignificant singular values according to the prior approximate error, the minimum number of elements c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Once the low-rank matrix is acquired, the parameters corresponding to the positions of the new sparse array with elements can be calculated by solving the following generalized eigenvalue problem [ 28 ], where and are obtained by deleting the first L rows and the last L rows of . Besides this, we can obtain eigenvalues more computationally efficient by solving the following equation where and are obtained by removing the first L rows and the last L rows of which contain only principal right singular vectors of .…”
Section: Proposed Synthesis Methods For Sparse Fdamentioning
confidence: 99%
See 1 more Smart Citation
“…Once the low-rank matrix is acquired, the parameters corresponding to the positions of the new sparse array with elements can be calculated by solving the following generalized eigenvalue problem [ 28 ], where and are obtained by deleting the first L rows and the last L rows of . Besides this, we can obtain eigenvalues more computationally efficient by solving the following equation where and are obtained by removing the first L rows and the last L rows of which contain only principal right singular vectors of .…”
Section: Proposed Synthesis Methods For Sparse Fdamentioning
confidence: 99%
“…Similarly, another set of eigenvalues corresponding to the frequency offsets also can be obtained. Next, utilize the pairing algorithm in [ 28 ] to get the correct pairing of and . Finally the locations and frequency offsets of the resulting sparse SFDA can be given by where …”
Section: Proposed Synthesis Methods For Sparse Fdamentioning
confidence: 99%
“…The main CS-based algorithms are Bayesian compressive sampling (BCS) algorithms [ 20 , 21 , 22 ], focal under-determined system solver (FOCUSS) algorithms [ 23 , 24 ], and convex optimization algorithms [ 25 , 26 , 27 ]. Moreover, some shaped beam patterns (such as flat-top BP and asymmetric sidelobe BP) are employed in sparse array synthesis via CS-based methods [ 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…The challenge of determining optimum parameter values simultaneously stems from the nonlinear and nonconvex dependency of the array factor to the weights and the sensor positions [4]. In [13], the authors revealed that the synthesis of nonuniform array elements' positions, excitations, and phases is a complicated nonlinear problem which contains a number of decision variables. The performance of the employed optimization scheme is an important factor in the success of a pattern synthesis method, in terms of solution quality, computational load, and stability.…”
Section: Introductionmentioning
confidence: 99%